Clinical anatomy of adrenal blood supply in different aged groups - M. S. Mitrofanova (Бюллетень сибирской медицины)
Renal blood supply sources of adrenals in the norm are studied in the work as well as blood supply peculiarities of unilateral adrenal and kidney in renal artery stenosis are revealed. It is concluded that including the study of adrenal arteries into angiographic algorithm in case of renal artery stenosis is of necessity.